2012
DOI: 10.1111/j.1365-2249.2011.04520.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of interferon-γ-, interleukin (IL)-17- and IL-22-expressing CD4 T cells, IL-22-expressing granulocytes and proinflammatory cytokines during latent and active tuberculosis infection

Abstract: SummaryIn this study, we investigated the role and expression of T helper type 17 (Th17) cells and Th17 cytokines in human tuberculosis. We show that the basal proportion of interferon (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 67 publications
9
56
1
1
Order By: Relevance
“…These results correlate with those of van Hamburg et al [122], who investigated the effects of the Th17 response on IL-22 in rheumatoid arthritis. As with Cowan et al [85], the levels of IL-22 were negatively correlated with the progression of disease; an interaction primarily mediated by Th17. This suggests that the Th17 response is modulated over time, such that the initial reaction to infection is one of concentrated and coordinated antimicrobial activity.…”
Section: Modulation Of the Immune Responsesupporting
confidence: 52%
See 3 more Smart Citations
“…These results correlate with those of van Hamburg et al [122], who investigated the effects of the Th17 response on IL-22 in rheumatoid arthritis. As with Cowan et al [85], the levels of IL-22 were negatively correlated with the progression of disease; an interaction primarily mediated by Th17. This suggests that the Th17 response is modulated over time, such that the initial reaction to infection is one of concentrated and coordinated antimicrobial activity.…”
Section: Modulation Of the Immune Responsesupporting
confidence: 52%
“…Qiu et al [121] showed a depletion of IL-22 secretion in CD4+ T cells associated with Mtb infection. Cowan et al [85] found that both the Th17 response and IL-22 were differentially induced and observed a correlation between down regulation of IL-22 and progression of infection. These results correlate with those of van Hamburg et al [122], who investigated the effects of the Th17 response on IL-22 in rheumatoid arthritis.…”
Section: Modulation Of the Immune Responsementioning
confidence: 99%
See 2 more Smart Citations
“…IL-17 is an important cytokine in mycobacterial infection; it not only contributes to the formation of granulomas, but also controls bacterial growth (Khader et al, 2007;Cruz et al, 2010;Torrado and Cooper, 2010;Cowan et al, 2012). RORgt was significantly induced at day 20 post infection, but decreased thereafter.…”
Section: Discussionmentioning
confidence: 99%